Condensed Matter Physics - Finley,Jaron [Ed.] (New York : Will Ford Press, 2017)
Condensed matter physics is the study of matter in various states of condensation. It examines the properties of condensed matter by applying the varied laws of physics. The topics included in this text present the dynamic research that is taking place in this field. The objective of this book is to give a general view of the different areas of condensed matter physics and its applications. It strives to provide a fair idea about this discipline and to help develop a better understanding of the latest advances within this field. This book is a vital tool for all researching or studying condensed matter physics as it gives incredible insights into emerging trends and concepts.
Keywords: Condensed matter; Physics